A critical comparison of pyrolysis of cellulose, lignin, and pine sawdust using an induction heating reactor. (1st June 2016) - Muley, Pranjali D.; Henkel, Charles; Abdollahi, Kamran K.; Marculescu, Cosmin; Boldor, Dorin
Highlights: Pine sawdust, lignin, and cellulose were pyrolyzed using induction heating reactor. Increasing temperature (500–700 °C) increased gas yield and decreased liquid yield. Cellulose had higher bio-oil yields than lignin; lignin had highest char yields. Cellulose bio-oil was rich in anhydrosugars; bio-oil from lignin was rich in phenols. Overall net positive energy output was achieved for all biomass types and the induction heating reactor. Abstract: Fast pyrolysis of pinewood sawdust and two of its major components, namely lignin and cellulose was carried out using a laboratory scale induction-heating reactor. The effect of five different temperatures (500, 550, 600, 650 and 700 °C) was tested on the product yield and quality. The products were characterized to evaluate the water content, elemental composition, chemical composition and energy content. The char yield decreased with temperature for all of the biomasses. The maximum liquid yield of 55.28% was achieved at 600 °C for pine sawdust, and the highest liquid yields for cellulose and lignin were obtained at 500 °C. Water content in the liquid fraction decreased as reaction temperature increased. The GC–MS revealed that the bio-oil from cellulose was rich in anhydrosugars while majority of the liquid from lignin had high phenolic contents. Analysis of the gas fraction shows that as the temperature increases the gas yield increases, which, when paired with the declining char masses, showed an increase in the biomass breakdown at higher temperatures. Liquid fraction from pine sawdust has the highest HHV with a peak at 550 °C.